El derecho al debido proceso en el procedimiento administrativo sancionador peruano en materia de defensa de la competencia ante Indecopi - Marcos Fernández, Francisco (2020)
Respect for the principle of “due process” in the administrative procedure envisaged for the application of the prohibitions on anticompetitive behavior established in Peru’s antitrust regulations before Indecopi is called into question due to the lack of separation between the investigative body (Technical Secretariat of the Commission of Free Competition) and the decision-making body (Commission of Free Competition). This article examines the issue from three perspectives. First, from the functional economic perspective, the organization and the administrative sanctioning procedure provided for in the Peruvian antitrust legislation are part of the public enforcement model that entrusts Indecopi (an agency divided into two units) with the enforcement of the prohibitions of anticompetitive conduct. Inevitably, this may lead to a confirmation bias (prosecutorial bias) -conscious or unconscious- of the final decisions adopted by the Commission. Secondly, from the perspective of the right to due process and the principle of impartiality in the European Convention on Human Rights (ECHR), Indecopi’s procedure would respect the requirements of the jurisprudence of the European Court of Human Rights (ECtHR). The author proposes that it is convenient to start with a reflection on how the jurisprudence has ruled that the extension of the human rights of the ECHR to legal persons (corporate human rights) should be examined in each case. Thirdly, from the perspective of comparative law, there are competition authorities with administrative procedures and organizations in other countries that have similarities with those followed by Indecopi. In particular, the European Commission and the Italian Autorità Garante de la Concorrenza (AGCM) are briefly mentioned.